A Description of A New Species of Leafhopper Genus Assuita Lindberg; 1969 (Hemoptera: Cicadellidae: Agalliinae) From Iraq - S. Al-Asady, Hassan; J. H. Al-Kiasy, Rawa’ (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study introduces description of a new species of leafhopper of genus Assuita Lindberg; 1969. This study includes external morphological characters and the spotting patterns and photos of vertex face pronotum, mesonotum, fore wing, hind wing and the shape of male abdominal abodeme, also aedeagus, connective, genital style and genital plate.